IMPROVEMENT OF PRODUCTION INFRASTRUCTURE OF THE REGION - E. Zubeeva (Publishing House of the State University of Management, 2018)
The article describes the process of creating a new block-modular boiler house in the town of Kirzhach of Vladimir region which was the result of the interaction of the stakeholders in the process of modernization of heat supply system in this city in the development of public-private partnership in the structure of LLC «Vladimiroblgaz», administration of Vladimir region and the city of Kirzhach and the State Corporation «Fund of assistance to reforming housing and communal services» of Russian Federation.